An alternative grading tool for enhancing assessment practice and quality assurance in higher education. Issue 1 (2nd January 2016) - Grainger, Peter; Weir, Katie
Abstract : Assessing student learning in university courses is commonly done using a rubric that arranges the assessment criteria and standards descriptors in a matrix style or grid format. This paper introduces an alternative style of grading tool known as the continua model of a guide to making judgements, which arranges assessment criteria based on a continuum of quality to look for in student work. The research participants attended focused professional development workshops then revised their criteria sheets based on the continua model and implemented them in teacher education classes. Interviews were conducted so that participants could reflect upon their experiences implementing the continua model and provide information about the design and efficacy of this new grading tool. The data suggests that the continua model has significant advantages over the traditional, matrix-style criteria sheet. These include being easier to identify and describe different standards, simplifying the grading process and streamlining moderation procedures.